A review of international clinical practice guidelines for the use of oxygen in the delivery room resuscitation of preterm infants. (6th September 2017) - Wilson, A; Vento, M; Shah, PS; Saugstad, O; Finer, N; Rich, W; Morton, RL; Rabi, Y; Tarnow‐Mordi, W; Suzuki, K; Wright, IM; Oei, JL
Abstract: Aim: To collate and assess international clinical practice guidelines (CPG) to determine current recommendations guiding oxygen management for respiratory stabilisation of preterm infants at delivery. Methods: A search of public databases using the terms 'clinical practice guidelines', 'preterm', 'oxygen' and 'resuscitation' was made and complemented by direct query to consensus groups, resuscitation expert committees and clinicians. Data were extracted to include the three criteria for assessment: country of origin, gestation and initial FiO2 and target SpO2 for the first 10 minutes of life. Results: A total of 45 CPGs were identified: 36 provided gestation specific recommendations (<28 to <37 weeks) while eight distinguished only between 'preterm' and 'term'. The most frequently recommended initial FiO2 were between 0.21 and 0.3 (n = 17). Most countries suggested altering FiO2 to meet SpO2 targets recommended by expert committees, However, specific five‐minute SpO2 targets differed by up to 20% (70–90%) between guidelines. Five countries did not specify SpO2 targets. Conclusion: CPG recommendations for delivery room oxygen management of preterm infants vary greatly, particularly in regard to gestational ages, initial FiO2 and SpO2 targets and most acknowledge the lack of evidence behind these recommendations. Sufficiently large and well‐designed randomised studies are needed to inform on this important practice. Abstract :